Waste molasses alone displaces glucose-based medium for microalgal fermentation towards cost-saving biodiesel production. - Yan, D.; Lu, Y.; Chen, Y. F.; Wu, Q.
The by-product of sugar refinery-waste molasses was explored as alternative to glucose-based medium of Chlorella protothecoides in this study. Enzymatic hydrolysis is required for waste molasses suitable for algal growth. Waste molasses hydrolysate was confirmed as a sole source of full nutrients to totally replace glucose-based medium in support of rapid growth and high oil yield from algae. Under optimized conditions, the maximum algal cell density, oil content, and oil yield were respectively 70.9 g/L, 57.6 per cent, and 40.8 g/L. The scalability of the waste molasses-fed algal system was confirmed from 0.5 L flasks to 5 L fermenters. The quality of biodiesel from waste molasses-fed algae was probably comparable to that from glucose-fed ones. Economic analysis indicated the cost of oil production from waste molasses-fed algae reduced by 50 per cent. Significant cost reduction of algal biodiesel production through fermentation engineering based on the approach is expected.
Keywords: WASTE MOLASSES; MICROALGA CHLORELLA PROTOTHECOIDES; OIL; BIODIESEL